Nano-silica for enhancing corrosion resistance of kaolin-based geopolymer concrete - Ayman Ababneh; Abdelrahman Al-shouha; Nabil Al-Akhras; Faris Matalkah (Case Studies in Construction Materials)
To reduce the carbon dioxide emissions due to Portland cement production and to protect the steel reinforcement from corrosion, a modified geopolymer binder with nano-silica (SiO2) was developed in this paper. The effects of SiO2, curing duration, and temperature on kaolin-based geopolymer concrete (GPC) corrosion resistance were investigated. The SiO2 particles were used as an additive to the kaolin-based geopolymer with different percentages (0, 4, 6, and 8 %) by weight of kaolin. Furthermore, the SiO2 was also used as a coating layer for steel reinforcement through dip-coating methods. The reinforced GPC Prisms were exposed to accelerated corrosion using an electrical current. The effect of SiO2 on the corrosion of steel reinforcement was evaluated using ultrasonic pulse velocity (UPV), half-cell potential (HCP), visual inspection, and pull-out test. The results revealed that the highest corrosion resistance was found at a 0.5 Molarity SiO2 concentration with a corrosion protection index of 48 % and weight loss of 7 %. Moreover, the results of UPV, HCP, and pull-out tests revealed that the bars coated with SiO2 exhibited higher UPV and HCP, higher toughness and stiffness by 82 % and 75 %, respectively, and 45 % lesser damage index (DI) when compared to uncoated bars.